EMOTION CONTROL STRATEGIES IN EARLY CHILDHOOD THROUGH PLAY THERAPY - Ritonga, Ristra Sandra; Nofianti, Rita; Arifin, Daud; Patuzahra, Sabrina (Proceeding International Seminar of Islamic Studies, 2024)
This study explores the strategies for controlling emotions in early childhood through the implementation of play therapy. Emotional regulation is a critical aspect of a child's development, significantly impacting their social interactions and overall well-being. Play therapy, as an evidence-based intervention, provides a safe and structured environment for children to express their emotions, develop coping mechanisms, and improve emotional intelligence. This research examines various play therapy techniques and their effectiveness in helping young children manage emotions such as anger, fear, and sadness. Through qualitative analysis, the study identifies key components of successful play therapy sessions, including the role of the therapist, the types of play activities used, and the outcomes observed in children's emotional behavior. The findings suggest that play therapy is a valuable tool for early childhood educators and therapists in promoting healthy emotional development, reducing behavioral issues, and enhancing children's ability to navigate complex emotional experiences. This research contributes to the growing body of knowledge on the benefits of play therapy and underscores its importance in early childhood education and mental health practices.